Protein Z-Dependent Regulation of Coagulation - Broze, George J., Jr. (Thrombosis and Haemostasis, 2001)
Protein Z (PZ) is a 62 kDa vitamin K-dependent plasma protein that serves as a cofactor for the inhibition of factor Xa by protein Z-dependent protease inhibitor (ZPI). ZPI is a recently identified 72 kDa member of the serpin superfamily of proteinase inhibitors that contains a tyrosine at its reactive center. PZ circulates in plasma in a complex with ZPI. Inhibition of factor Xa by ZPI in the presence of phospholipids and Ca++ is enhanced 1000-fold by PZ, but ZPI also inhibits factor XIa in a process that does not require PZ, phospholipids or Ca++. ZPI activity is consumed during coagulation through proteolysis mediated by factor Xa with PZ and factor XIa. Concomitant PZ deficiency dramatically increases the severity of the prothrombotic phenotype of factor VLeiden mice. Studies to determine the potential roles of PZ and ZPI deficiency in human thrombosis are in progress.
Keywords: Factor Xa; factor XIa; serpin; proteinase inhibitor